2016
DOI: 10.1093/tropej/fmw081
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels in Malnourished Children under 5 Years in a Tertiary Care Center at Muhimbili National Hospital, Dar es Salaam, Tanzania—A Cross-sectional Study

Abstract: : The high prevalence of VDD in malnourished children underlines the need for active surveillance and aggressive management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…The Generation R study, a large multi-ethnic cohort of 6-year-olds in the Netherlands, found that children who were underweight (defined by BMI Z- score) had a higher risk of vitamin D deficiency (<50 nmol/l) compared with normal-weight children ( 21 ) . Another study in a tertiary care centre in Tanzania found that 30·6 % (41/134) of children <5 years old had vitamin D deficiency (defined as <50 nmol/l) and that children with marasmus were more likely to have vitamin D deficiency compared with children with kwashiorkor or marasmic kwashiorkor ( 22 ) .…”
mentioning
confidence: 99%
“…The Generation R study, a large multi-ethnic cohort of 6-year-olds in the Netherlands, found that children who were underweight (defined by BMI Z- score) had a higher risk of vitamin D deficiency (<50 nmol/l) compared with normal-weight children ( 21 ) . Another study in a tertiary care centre in Tanzania found that 30·6 % (41/134) of children <5 years old had vitamin D deficiency (defined as <50 nmol/l) and that children with marasmus were more likely to have vitamin D deficiency compared with children with kwashiorkor or marasmic kwashiorkor ( 22 ) .…”
mentioning
confidence: 99%
“…Ten papers were finally included in the study ( Fig. 1 ) [ [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. After identification of the available papers, the papers were categorized in to two (healthy and sick) based on the type of population used to study.…”
Section: Resultsmentioning
confidence: 99%
“…52,53 Malnutrition is a well-recognized cause of vitamin D deficiency worldwide. 54 In general, it was believed that persons with diabetes are at significant risk for vitamin D insufficiency or deficiency. Reasons for this include diet, lack of sun exposure, obesity, renal impairment, and genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%